2015
DOI: 10.5897/ajar2015.9567
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rice varieties in relation to nitrogen levels under irrigated condition

Abstract: The field experiment was conducted at the research farm College of Agriculture, JNKVV, Rewa M.P. during kharif season 2011 to study the performance of rice varieties and relation to nitrogen level under irrigated conditions. Twenty one treatment combinations, comprising three nitrogen levels (40, 80 and 120 kg ha-1), followed by IET 21278 (56.78 q ha-1) and obtained net income Rs. 40871 ha-1 and Rs. 38983 ha-1 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Whereas much higher number of tillers were recorded through application of 150 kg N ha -1 as reported by Ramesh et al (2009). Similarly, positive response to Nitrogen application has been reported by Shukla et al (2015) at 120 kg N ha -1 with effective tillers (238.50 m -2 ), Kumar et al (2017) at 150 kg/ha (9.25 EBT hill -1 ) under aerobic condition and Dahipahle and Singh (2018) at 180 kg N ha -1 (12.6 EBT hill -1 ) under puddle soils.…”
Section: Plant Heightsupporting
confidence: 55%
See 3 more Smart Citations
“…Whereas much higher number of tillers were recorded through application of 150 kg N ha -1 as reported by Ramesh et al (2009). Similarly, positive response to Nitrogen application has been reported by Shukla et al (2015) at 120 kg N ha -1 with effective tillers (238.50 m -2 ), Kumar et al (2017) at 150 kg/ha (9.25 EBT hill -1 ) under aerobic condition and Dahipahle and Singh (2018) at 180 kg N ha -1 (12.6 EBT hill -1 ) under puddle soils.…”
Section: Plant Heightsupporting
confidence: 55%
“…Saha et al (2017) found 90 kg N ha -1 producing significantly higher (4.96 t ha -1 ) straw yield. Shukla et al (2015) found a nitrogen dose of 120 kg N ha -1 exhibiting the maximum harvest index (34.84%). Saha et al (2017) also reported higher (44.80) value of harvest index at 90 kg N ha -1 followed by 60 kg N ha -1 (40.80 %) and 30 kg N/ha (36.80%).…”
Section: Number Of Filled Grainsmentioning
confidence: 93%
See 2 more Smart Citations
“…Más aún, el cultivo de arroz puede acumular alrededor de 7.3 t ha -1 con 10 % de fertilización recomendada del paquete tecnológico de INIFAP. Resultados similares fueron reportados por Shukla et al (2015) y Jana et al (2017), los cuales registraron mayor altura de planta al aumentar los niveles de fertilización. Investigaciones han demostrado que el nitrógeno potencializa el crecimiento de arroz y la mayor concentración de este elemento se encuentra en hojas y tallos (Wang et al 2018).…”
Section: Biomasa Fresca Y Altura De Plantaunclassified